Severity of acute pancreatitis in patients with inflammatory bowel disease in the era of biologics: A propensity‐score‐matched analysis using a nationwide database in Japan. Issue 1 (28th December 2022) - Moroi, Rintaro; Tarasawa, Kunio; Ikeda, Mio; Matsumoto, Ryotaro; Shimoyama, Yusuke; Naito, Takeo; Takikawa, Tetsuya; Shiga, Hisashi; Hamada, Shin; Kakuta, Yoichi; Kikuta, Kazuhiro; Fushimi, Kiyohide; et al.
Abstract: Background and Aim: Acute pancreatitis (AP) is a rare extraintestinal manifestation of inflammatory bowel disease (IBD). Several studies from Western countries have reported that the severity of AP in patients with IBD is similar to that in the general population; however, its severity in patients from Eastern countries in the era of biologics remains unclear. This study aimed to investigate the severity of AP in patients with IBD and the effect of biologics on the severity of AP using a nationwide database. Methods: We divided 1138 eligible AP admissions from the Diagnosis Procedure Combination database system into IBD and non‐IBD groups after propensity score matching, and compared the severity of AP. We divided the IBD group into ulcerative colitis (UC) and Crohn's disease (CD) subgroups and compared each with the non‐IBD group. Logistic regression analysis was conducted to identify the clinical factors affecting acute pancreatitis. Results: IBD and UC groups had lower rate of severe AP compared to the non‐IBD group (13.7% vs 28.3%, P  < 0.0001 and 11.0% vs 28.3%, P  < 0.0001, respectively). There were no differences in the rates of severe AP between the CD and non‐IBD groups. Multivariate analysis showed that biologics did not affect the severity of AP. Conclusion: The severity of AP in patients with IBD may be lower than that in the general population; biologics for IBD may not worsen its severity. Further prospective studies are required to clarify the severity of AP in patients with IBD. Abstract : We investigated the impact of concomitant inflammatory bowel disease (IBD) on the clinical severity of acute pancreatitis (AP) using a nationwide database in Japan. After propensity score matching, the occurrence of severe AP in the IBD group was significantly lower than that in the non‐IBD group (13.7% vs 28.3%, P  < 0.0001). Our results indicate that the severity of AP in patients with IBD may be lower than that in the general population.